A231 URGENT PRIORITY ENDOSCOPY PATHWAY IN A HIGH VOLUME CENTRAL ACCESS MODEL: OPTIMIZING GASTROENTEROLGY CARE FOR THE SICKEST PATIENTS. (1st March 2018) - Mazurek, M S; Novak, K L; Heather, V C; Heather, G S; Swain, M; Belletrutti, P J
Abstract: Background: Increasing demand for endoscopic evaluation of digestive diseases in Canada challenges the capacity of gastroenterologists to provide timely access to care. Hence, the accurate identification of high risk patients requiring expedited care because of significant morbidity is essential. Yet, predicting significant pathology based on the referral history alone is limited. At our institution, a single point of entry model is used to centralize intake and improve referral management. Recently, due to increased demand, an Urgent-Priority Endoscopy (UPE) pathway was created to enhance access for patients requiring the most urgent diagnostic endoscopies. Aims: This study aims to assess the effectiveness of the UPE pathway in providing appropriate patient triage and timely access to endoscopic assessment. Methods: All patients triaged to the UPE pathway from December 1, 2016–May 31, 2017 were identified. Anonymized patient data, including demographics, initial referral date and indication were abstracted and correlated with endoscopic and histopathologic findings. Results: During the six-month study period, from a total referral volume of 11 116 cases, 131 were triaged directly to endoscopy through the UPE pathway. Patients underwent esophagogastroduodenoscopy (101), colonoscopy (27), both (1), or sigmoidoscopy alone (1). The median wait time from referral to procedure was 4.1 weeks (range 1–55.1). Median age was 60 years (range 19–92) with 69 (52.7%) male patients. The most common indication was dysphagia (n=50, 38.1%), of which 40 patients (80%) had an attributable cause identified: gastroesophageal reflux-related (38%), benign structural causes (24%), motility disorders (6%) or malignancy (6%). Other reasons for referral included abnormal imaging findings (26%), suspected upper gastrointestinal bleeding (19%), anemia (3.8%), mass on digital rectal exam (2.3%), and weight loss (2.3%). Overall, an attributable cause for the referring indication was found in 87/131 patients for a diagnostic yield of 66%. A malignant cause was found in 10 patients (7.6%), namely adenocarcinoma of the colon (4), stomach (4), esophagus (1), and 1 gastric lymphoma. Conclusions: Triage to the UPE pathway via a single point of entry model provided expedited assessment for alarming gastrointestinal symptoms and identified significant pathology in the majority of patients. Yet, one third of patients had a normal endoscopy. Improved referral quality—through access to electronic medical records, for example, or mandated objective measures of significant disease upon referral—could further improve the triage accuracy and facilitate timelier access to care. Funding Agencies: Division of Gastroenterology, University of Calgary